2013
DOI: 10.1083/jcb.201302040
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-1–syntaphilin coupling mediates activity-dependent regulation of axonal mitochondrial transport

Abstract: Syntaphilin mediates the activity-dependent immobilization of axonal mitochondria by physically displacing KIF5 from the Miro–Trak transport complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
212
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(226 citation statements)
references
References 44 publications
10
212
2
2
Order By: Relevance
“…GFP-labeled mitochondria in ALM neuronal processes appear as sphere and rod-shaped organelles of varying size distributed at distinct intervals (Fig. 1A), similar to axonal mitochondria in mammalian neurons (Kang et al, 2008;Chen and Sheng, 2013). Mitochondria in the adult neuronal cell bodies form a filamentous tubular network that encircles the soma perimeter (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GFP-labeled mitochondria in ALM neuronal processes appear as sphere and rod-shaped organelles of varying size distributed at distinct intervals (Fig. 1A), similar to axonal mitochondria in mammalian neurons (Kang et al, 2008;Chen and Sheng, 2013). Mitochondria in the adult neuronal cell bodies form a filamentous tubular network that encircles the soma perimeter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While the majority of mitochondria are stationary during a 5 min recording, some move along processes in a "stop and go" pattern ( Fig. 5A) similar to axonal mitochondria of mammalian and fly larvae neurons (Kang et al, 2008;Mondal et al, 2011;Chen and Sheng, 2013). Consistent with an ex vivo study in mouse nerve explants (Misgeld et al, 2007), we observed that motile mitochondria were significantly shorter than the stationary ones: the average length of motile mitochondria at 1DA is 1.1 Ϯ 0.4 m (mean Ϯ SEM; n ϭ 103), compared to 2.3 Ϯ 0.06 m when stationary (n ϭ 306, p Ͻ 0.01).…”
Section: Mitochondrial Trafficking In Distal Alm Process Declines Promentioning
confidence: 99%
“…In support of this model, depletion of the Miro adaptor Trak1 is reported to decrease axonal branching (24). In addition, a specific kinase pathway was recently shown to support axon branching in cortical neurons by promoting immobilization of mitochondria at presynaptic sites via the docking protein syntaphilin (39,(46)(47)(48). Although the neuronal defects described here are the most likely cause of early mortality in Miro1 KO mice, changes in additional neuronal populations or tissues may also contribute to this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the second model, the KIF5 tail is linked to Miro1 via TRAK2 in a Ca 2 + -independent manner, freeing the motor domain to engage with microtubules. Ca 2 + binding to the EF-hand [40], (ii) KIF5 remains bound to the Miro1/TRAK2 complex upon uncoupling [55], or (iii) detachment from KIF5 occurs with subsequent interaction of the mitochondrial tether syntaphilin (SNPH) [61].…”
Section: Mitochondrial Trafficking In Astrocytic Processesmentioning
confidence: 99%